PERAN HUKUM ISLAM DALAM PEMBANGUNAN HUKUM NASIONAL - Delisya Fransiska Simamora; Afni Nur Fadilah, Maniar Clarita Nainggolan, Arinda Risna Cherylia Siregar, Novita Ramdaini, Ronaldo (Adisam Publisher, 2023)
Islamic law is a legal system that originates from the holy book or divine revelation. Islamic law has played a role in establishing legal norms and values that apply to the heterogeneity of Indonesian society. Every attempt to legislate Islamic sharia in Indonesia always faces controversy which is not only technical legal in nature but also involves political issues. In order for Islamic law and customary law to be effective in a country, both must be positive by incorporating legal principles into statutory regulations. The research methodology used in this research is normative juridical, namely an approach that refers to applicable laws and regulations. Research findings showing the role of Islamic law in the development of Indonesian law can be seen from two perspectives. First, the extent to which Islamic law is involved in the daily lives of community members who are in the development process, ultimately connects to the process mentioned above. Second, the causal relationship between Islamic law and the legal development process in Indonesia. Indonesian national law was abolished according to the state philosophy of Pancasila. National law serves Indonesia's national interests, including diversity values, especially religious beliefs. Therefore, it is clear that religious law (Islamic law) must be included in Indonesian national law. Islamic law automatically applies to Muslims, regardless of their nationality or location. Islamic law is part of domestic law that applies to a particular nation in a particular country.